2018
DOI: 10.1097/mol.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained reciprocal regulation of diabetes and lipoproteins

Abstract: Purpose of review Type 2 diabetes is associated with a characteristic dyslipidemia that may exacerbate cardiovascular risk. The causes of, and the effects of new antihyperglycemia medications on, this dyslipidemia, are under investigation. In an unexpected reciprocal manner, lowering LDL-cholesterol with statins slightly increases the risk of diabetes. Here we review the latest findings. Recent findings The inverse relationship between LDL-cholesterol and diabetes has now been confirmed by multiple lines of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 98 publications
2
8
0
Order By: Relevance
“…Previous research into loci that jointly alter the risk for LDL-C and T2D has focused on the genomic targets of lipid-lowering medications, in the hope that these analyses will give specific insights into associated T2D risk. Our analyses confirmed that variants in HMGCR (36) and NPC1L1 (19) are associated with lower LDL-C and increased T2D risk. On the other hand, our analyses did not identify variants at PCSK9 .…”
Section: Discussionsupporting
confidence: 76%
“…Previous research into loci that jointly alter the risk for LDL-C and T2D has focused on the genomic targets of lipid-lowering medications, in the hope that these analyses will give specific insights into associated T2D risk. Our analyses confirmed that variants in HMGCR (36) and NPC1L1 (19) are associated with lower LDL-C and increased T2D risk. On the other hand, our analyses did not identify variants at PCSK9 .…”
Section: Discussionsupporting
confidence: 76%
“…Previous research into loci that jointly alter the risk for circulating LDL-C and T2D has focused on the genomic targets of lipid-lowering medications in the hope that these analyses will give specific insights into associated T2D risk. On one hand, our analyses confirmed that variants in HMGCR ( 41 ) and NPC1L1 ( 14 ) are associated with lower circulating LDL-C and increased T2D risk. On the other hand, our analyses did not identify variants at PCSK9 .…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, various inhibitors of dipeptidyl peptidase-4 have additional effects on the lipid profile; for instance, anagliptin has a greater LDL cholesterol-lowering effect than sitagliptin (14). Incretin-based therapies lower TG levels (15), whereas inhibitors of sodium-glucose transport protein 2 may slightly increase both HDL and LDL cholesterol (15). Regardless, both glucagon like peptide 1 receptor agonists and oral sodium-glucose transport protein 2 inhibitors clearly reduce ASCVD outcomes via numerous incompletely defined mechanisms (16).…”
Section: Effect Of Nonlipid Interventions On Diabetic Dyslipidemiamentioning
confidence: 99%